Effects of Reinforcing Fiber and Microsilica on the Mechanical and Chloride Ion Penetration Properties of Latex-Modified Fiber-Reinforced Rapid-Set Cement Concrete for Pavement Repair - Woong Kim; Jong-Chan Jeon; Byung-Hwan An; Joo-Ha Lee; Hae-Do Kim; Chan-Gi Park (Advances in Materials Science and Engineering)
This study evaluated the influence of reinforcement fiber type and microsilica content on the performance of latex-modified fiber-reinforced roller-compacted rapid-hardening cement concrete (LMFRCRSC) for a concrete pavement emergency repair. Experimental variables were the microsilica substitution ratio (1, 2, 3, and 4%), and the reinforcement fiber (jute versus macrosynthetic fiber). In the tests, compressive, flexural, and splitting tensile strength; chloride ion penetration resistance; and abrasion resistance were assessed. From the compressive and flexural strength tests with microsilica substitution, the 4-hour curing strength decreased as the microsilica substitution ratio increased. From the chloride ion penetration test, as the microsilica substitution ratio increased, chloride ion penetration decreased. The abrasion resistances increased with the substitution ratio of microsilica increase. Based on these test results, microsilica at a substitution ratio of 3% or less and macrosynthetic fiber as the reinforcement improved the performance of LMFRCRSC for a concrete pavement emergency repair and satisfied all of the target strength requirements.